Is percutaneous endoscopic lumbar discectomy necessary for learning the unilateral biportal endoscopy technique? - Yiwei Xie; Yicheng Chen; Qifeng Yu; Yi Liu; Xin Gu; Xiaojian Ye (Frontiers in Surgery)
ObjectiveThis study aims to investigate the effect of prior percutaneous endoscopic lumbar discectomy (PELD) surgical experience on the learning curve of the unilateral biportal endoscopy (UBE) technique.MethodsA total of 200 patients undergoing single-segment UBE surgery were enrolled. The procedures were performed by four surgeons, who were divided into two groups based on whether they had prior PELD experience (Group A: with; Group B: without). Proficiency in UBE technique was defined as a surgery time of less than 80 min. The cumulative sum analysis (CUSUM) method was used to analyze each surgeon's learning curve. Clinical efficacy was evaluated using patient-reported outcomes (PROs) after surgery: Modified Macnab, VAS-leg, VAS-back, and ODI scores. Follow-up information was obtained 12 months postoperatively.ResultsThe number of cases required for Group A surgeons to achieve proficiency were 17 and 18, significantly fewer than the 25 and 27 cases for Group B surgeons. No significant differences in clinical outcomes were observed between the two groups. The complication rates for Group A and Group B were 5 and 14, respectively.ConclusionPrior PELD surgical experience facilitates learning the UBE technique. This experience further aids in shortening surgical times, lowering complication rates, and decreasing the need for reoperation.